Adhesive behaviour of bonded paper layers: Mechanical testing and statistical modelling. (May 2016) - Borri, Claudia; Paggi, Marco; Reinoso, José; Borodich, Feodor M
In this study, an experimental methodology based on micromechanical testing inside a scanning electron microscope is proposed to characterise bonding of paper layers connected by wet pressing. The peeling force–displacement evolution law that characterises the delamination of micromechanical double cantilever beam specimens of paper tissue have been extracted from such peeling tests. It is observed that the force–displacement evolution curve achieves a steady-state value related to the effective adhesive energy of the interface. This behaviour is explained by examining the complex load transfer mechanism between the layers exerted by cellulose fibrils. A statistical approach is used for the computation of the effective adhesive energy. It is argued that the observed force–displacement evolution law may be satisfactory described by a stochastic model that depends on the distribution function of the fibrils strength, and on two geometrical distribution functions related to the in-plane and out-of-plane fibrils angles with respect to the undeformed interface configuration. Some applications of the proposed model are demonstrated on examples.